Didactic activities to improve the Learning of English reading comprehension in 5th grade students = Actividades didácticas para mejorar el aprendizaje de la comprensión lectora en inglés en alumnos de 5 ° grado - Mojica Cáceres, Cesia Elizabeth; De León, Rodrigo (Panamá , Panamá : UDELAS, 2019)
This project is entitled didactic activities to improve the learning of English reading comprehension in fifth grade students of the Escuela Bilingüe Reino de los Países bajos Horlanda Morning shift. IDIOMA ESPAÑOL Este proyecto se titula Actividades didácticas para mejorar el aprendizaje de la comprensión lectora en inglés en alumnos de quinto grado de la Escuela Bilingüe Reino de los Países Bajos Horlanda Turno de mañana.
TABLE OF CONTENT CHAPTER I: REFERENCIAL FRAMEWORK OF THE PROJECT CHAPTER II: THEORETICAL FUNDATION OF THE PROJECT CHAPTER III: ANALYSIS AND INTERPRETATION OF RESULTS CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHIC REFERENCES APPENDIX
Presentada para optar al Título de English Language Teaching
Incluye Bibliografía
No se presta domicilio
Prohibido fotocopiar
Keywords: ENGLISH LANGUAGE TEACHING; IDIOMA INGLÉS - ENSEÑANZA; COLEGIO DE EDUCACIÓN ESPECIAL Y ESCUELA DE PEDAGOGÍA